Protective factors for the risk of suffering intimate partner violence in help-seeking women survivors from a social organization in Chile - Benjumeda Wynhoven, Isabel; Yago Alonso, Carmen (Frontiers in Sociology, 2024)
ObjectiveIntimate partner violence (IPV) is a major public health problem in Latin America. The present study investigates the protective factors that contribute to minimizing the risk of exposure to IPV analyzing different variables in a sample of Chilean women victims of IPV.MethodsWe used data from the Cicatrices Foundation, a nonprofit Chilean organization providing psychological support to IPV victims. Relevant variables for IPV prevention were identified analyzing a database containing all the information reported by victims during a structured interview. A final sample of 444 women suffering IPV was used in the present study.ResultsLogistic regression analysis was calculated in order to make predictions related to IPV protective factors, showing that having a support network (OR = 2.85), treatment compliance (OR = 2.05) and being younger (OR = 0.95) increased the probability of not living with the aggressor. Another logistic regression analysis was calculated in order to predict IPV victims´ health taking medication intake as an indicator. A significant association was observed between this variable and working outside (p = 0.002) and between mediation intake and age (p < 0.001), with an OR of 1.987 and 0.93, respectively. Working outside and being younger were identified as protective factors against consuming medication.ConclusionTo the best of our knowledge, this is one of the first studies conducted in Chile on the prevention of IPV in a sample of victims seeking for help. Our results will contribute to guide policy makers, researchers and other women in the prevention of potential risks for IPV.